2018
DOI: 10.1371/journal.ppat.1007299
|View full text |Cite
|
Sign up to set email alerts
|

Infection with flaviviruses requires BCLXL for cell survival

Abstract: BCL2 family proteins including pro-survival proteins, BH3-only proteins and BAX/BAK proteins control mitochondria-mediated apoptosis to maintain cell homeostasis via the removal of damaged cells and pathogen-infected cells. In this study, we examined the roles of BCL2 proteins in the induction of apoptosis in cells upon infection with flaviviruses, such as Japanese encephalitis virus, Dengue virus and Zika virus. We showed that survival of the infected cells depends on BCLXL, a pro-survival BCL2 protein due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 74 publications
1
30
0
1
Order By: Relevance
“…Another striking phenomenon during JEV infection was the extensive activation of all currently known PCD pathways, especially apoptosis, pyroptosis, and necroptosis. JEV infection induces apoptosis in various cell types [20][21][22][23][24], while the impact of JEV infection on the apoptosis of macrophages has not yet been reported. Our results show that JEV infection stimulated macrophage apoptosis by activating both extrinsic and intrinsic apoptosis pathways.…”
Section: Discussionmentioning
confidence: 98%
“…Another striking phenomenon during JEV infection was the extensive activation of all currently known PCD pathways, especially apoptosis, pyroptosis, and necroptosis. JEV infection induces apoptosis in various cell types [20][21][22][23][24], while the impact of JEV infection on the apoptosis of macrophages has not yet been reported. Our results show that JEV infection stimulated macrophage apoptosis by activating both extrinsic and intrinsic apoptosis pathways.…”
Section: Discussionmentioning
confidence: 98%
“…Suzuki and colleagues proposed that Flavivirus infection induces delayed cell apoptosis and consequently virus spread to neighboring cells leading to higher viral loads and disease severity. Bcl-xL inhibition accelerates apoptosis leading to enhanced viral clearance through macrophage phagocytosis 46 .…”
Section: Discussionmentioning
confidence: 99%
“…A control of the stability and degradation of Bcl-2 is therefore a key in the subtle balance that takes place between pro and anti-apoptotic suits to determine the cell's fate [40]. Previous study showed the importance of Bcl-xL for cells survival, in deficient Bcl-2 cells during ZIKV infection [41], but here we cannot exclude a role for Bcl-2 and/or Bcl-xL protein as our model express these two anti-apoptotic proteins. As we used cycloheximide or blasticidin in our assays, we can therefore assume that the mechanism implemented by ZIKV does not involve a "de novo" synthesis of proteins.…”
Section: Discussionmentioning
confidence: 99%